Curcumin inhibits ovarian cancer progression by regulating circ-PLEKHM3/miR-320a/SMG1 axis - Sifan Sun; Hailiang Fang (BMC, 2021)
Abstract Background Curcumin has a potential therapeutic role in ovarian cancer. However, whether curcumin plays anti-cancer role in ovarian cancer by mediating the circular RNA (circRNA)/microRNA (miRNA)/mRNA network is still unclear. Methods The expression of circ-PLEKHM3, miR-320a, and suppressor of morphogenesis in genitalia 1 (SMG1) was detected via qRT-PCR. Cell viability, colony-formation ability and apoptosis were analyzed via cell counting kit-8 assay, colony formation analysis, and flow cytometry. Protein expression was measured using western blot. The in vivo experiments were performed using a xenograft model. Target association was evaluated via dual-luciferase reporter analysis and RIP assay. Results Curcumin suppressed ovarian cancer cell proliferation and promoted apoptosis. Circ-PLEKHM3 was downregulated in ovarian cancer, and its expression could be promoted by curcumin treatment. Circ-PLEKHM3 overexpression exacerbated the effect of curcumin on ovarian cancer cell proliferation and apoptosis, as well as anti-tumor effect. MiR-320a was targeted by circ-PLEKHM3. The inhibition effect of circ-PLEKHM3 overexpression on cell proliferation and the enhancing effect on cell apoptosis could be reversed by miR-320a mimic. SMG1 was targeted by miR-320a, and its knockdown also reversed the regulation of miR-320a inhibitor on the proliferation and apoptosis of ovarian cancer cells. In addition, circ-PLEKHM3 could upregulate SMG1 expression via sponging miR-320a. Conclusion Curcumin restrained proliferation and facilitated apoptosis in ovarian cancer by regulating the circ-PLEKHM3/miR-320a/SMG1 axis.